The Impact of Food Delivery Apps on Customer Perceived Value Among University Students - Varsha Ganatra; Rishikaysh Kaakandikar; Muhammad Izzuddin; Daisy Mui Hung Kee; Najihah Bt Zainuddin; Muhammad Az-Zahid Bukhari; Muhammad Azfar Nurhakim; Varsha Panwar (Journal of the Community Development in Asia (JCDA), 2021)
The number of food delivery apps users has increased nowadays due to the recent global pandemic situation of the coronavirus outbreak. Food delivery apps bring many benefits to the students and catering business. This paper aims to study the impact of food delivery apps on customer perceived value among university students. A quantitative approach was used in this study. Cross-sectional design used as the design of the study and the data will be gathered at one point in a time. Questionnaires used to collect the data from all respondents. The respondents were university students with the number of samples as many as 101 people. The results found how food delivery applications had an impact on customer perceived value among university students in Malaysia during the pandemic and it can be said that respondents gave a lot of positive feedback on food delivery service, where they believed in the products and service provided.